High fibrinogen levels are associated with poor survival in patients with liposarcoma - L. S. Peschek; Gerhard M. Hobusch; P. T. Funovics; M. Willegger; M. P. Schmid; G. Amann; W. Lamm; Th. Brodowicz; C. Ay; R. Windhager; J. Panotopoulos (Scientific Reports, 2023)
Abstract The aim of this study was to evaluate whether (preoperative) plasma levels of fibrinogen, an essential clotting and acute phase protein, are associated with the prognosis of patients with a liposarcoma, a subtype of sarcoma derived from adipose tissue. We performed a retrospective cohort study of 158 patients with liposarcoma treated at the Department of Orthopaedics of the Medical University of Vienna in Austria from May 1994 to October 2021. Kaplan–Meier curves as well as uni- and multivariable Cox proportional hazard models were performed to evaluate the association between fibrinogen levels and overall survival. Elevated fibrinogen was associated with adverse overall survival in cause specific hazards analysis of mortality (hazard ratio [HR] per 10 mg/dL increase: 1.04; 95% CI 1.02–1.06; p < 0.001). This association prevailed in multivariable analysis after adjustment for AJCC tumor stage (HR 1.03; 95% CI 1.01–1.05; p = 0.013). Increasing levels of fibrinogen, a routinely available and inexpensive parameter, predicts the risk of mortality in patients with liposarcoma.